Impacto de la adopción de las tecnologías de información y comunicación en la productividad en ventas de la asociación de fondos contra accidentes de tránsito de la región San Martín - Solano Linares, Edin Luis (2014)
The following research is related to how important the Informatics an Communication Technology (ICT) is for improving productivity and competitive of the Association of Traffic Accident Founds AFOCAT San Martín, which faces an important challenge to the economic develop of San Martin region and the country in a whole, on the basis that this research shows a low level of ICT management like Internet and computing apps, which come from a poor computing technology knowledge and its multiple advantages for process, team work, economic resources improvement in relation to ratability and other benefits to the company. At the same time, the company faces a growing competence. This research has as objective to evaluate the impact of the ICT in profits and productivity in Association of Traffic Accident Founds of San Martin, establishing the association among the ICT adoption degree and the productivity of AFOCAT San Martín. Correlation descriptive investigation design was use through the statistics contrast Chi Quadrant (X2), which shows that there is not significant relation in the use of ICT computing and Internet apps adoption in AFOCAT San Martin. According to the research results, it can be established that the usage of ICT in AFOCAT San Martin is categorized as “low level of use”, having a 38% of the whole sample, in spite, when we measured the impact generated for the level of use reached in the company productivity by using computing programs and Internet, divided into 15 productivity items, a positive result in a global level was reached around 44.4% that means “Good Impact”.